A human 3D immune competent full-thickness skin model mimicking dermal dendritic cell activation - Hölken, Johanna Maria; Friedrich, Katja; Merkel, Marion; Blasius, Nelli; Engels, Ursula; Buhl, Timo; Mewes, Karsten Rüdiger; Vierkotten, Lars; Teusch, Nicole Elisabeth (Frontiers in Immunology, 2023)
We have integrated dermal dendritic cell surrogates originally generated from the cell line THP-1 as central mediators of the immune reaction in a human full-thickness skin model. Accordingly, sensitizer treatment of THP-1-derived CD14 -, CD11c + immature dendritic cells (iDCs) resulted in the phosphorylation of p38 MAPK in the presence of 1-chloro-2,4-dinitrobenzene (DNCB) (2.6-fold) as well as in degradation of the inhibitor protein kappa B alpha (IκBα) upon incubation with NiSO4 (1.6fold). Furthermore, NiSO4 led to an increase in mRNA levels of IL-6 (2.4-fold), TNF-α (2-fold) and of . These results were confirmed on the protein level, with even stronger effects on cytokine release in the presence of NiSO4: Cytokine secretion was significantly increased for IL-8 (147-fold), IL-6 (11.8-fold) and IL-1β (28.8-fold). Notably, DNCB treatment revealed an increase for IL-8 (28.6-fold) and IL-1β (5.6-fold). Importantly, NiSO4 treatment of isolated iDCs as well as of iDCs integrated as dermal dendritic cell surrogates into our full-thickness skin model (SM) induced the upregulation of the adhesion molecule clusters of differentiation (CD)54 (iDCs: 1.2-fold; SM: 1.3-fold) and the co-stimulatory molecule and DC maturation marker CD86 (iDCs ~1.4-fold; SM:~1.5-fold) surface marker expression. Noteworthy, the expression of CD54 and CD86 could be suppressed by dexamethasone treatment on isolated iDCs (CD54: 1.3-fold; CD86: 2.1-fold) as well as on the tissueintegrated iDCs (CD54: 1.4-fold; CD86: 1.6-fold). In conclusion, we were able to integrate THP-1derived iDCs as functional dermal dendritic cell surrogates allowing the qualitative identification of potential sensitizers on the one hand, and drug candidates that potentially suppress sensitization on the other hand in a human 3D human skin model corresponding to the 3R principles ("replace", "reduce" and "refine").